2017
DOI: 10.4236/fns.2017.86048
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Protects Gut Barrier Function and Prevents Endothelial Cell Injury Induced by Ischaemia-Reperfusion

Abstract: Purpose: Gut permeability and microvascular injury following ischaemia/reperfusion (IR) have been implicated in the systemic inflammatory response syndrome (SIRS) and multiple organ failure (MOF). Taurine (TAU), a sulfurcontaining amino acid, is a powerful antioxidant and regulator of intracellular calcium and several studies have established that treatment with TAU protects cerebral, cardiac and testicular tissue from (IR) injury. This study investigates the protective effect of taurine in an experimental mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The benefits of perioperative treatment with immunonutrients are well documented and include reduction of postoperative complications, reduced loss of skeletal mass, modulated inflammatory response, and improved protein synthesis after surgery [19,20,21,22,23,24,25,26,27,28,29,30,31,32]. It is known that taurine supplementation augments immune function and protects the gut from intestinal barrier dysfunction induced by surgery [33]. The same phenomenon of complex immune dysfunction is seen in cancer patients and clinical data show a correlation between high-density leukocytic infiltration in solid tumors and poor patient outcomes.…”
Section: Update On Biologymentioning
confidence: 99%
“…The benefits of perioperative treatment with immunonutrients are well documented and include reduction of postoperative complications, reduced loss of skeletal mass, modulated inflammatory response, and improved protein synthesis after surgery [19,20,21,22,23,24,25,26,27,28,29,30,31,32]. It is known that taurine supplementation augments immune function and protects the gut from intestinal barrier dysfunction induced by surgery [33]. The same phenomenon of complex immune dysfunction is seen in cancer patients and clinical data show a correlation between high-density leukocytic infiltration in solid tumors and poor patient outcomes.…”
Section: Update On Biologymentioning
confidence: 99%
“…In addition, the protective effects on intestinal integrity, inflammation and oxidative stress were also found for other amino acids including serine, 46,47 tryptophan [48][49][50] and taurine. [51][52][53] Relative to age-matched CON mice, therefore, lower levels of these amino acids in the jejunum of T1D mice may indicate jejunum dysfunction, affecting the onset and progression of diabetes and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…After intestinal I/R, acute lung injury occurs as a major complication, leading to high mortality rate [23].The damaged intestine releases mtDNA, accelerating the release of in ammatory cytokines and chemical chemokines,whicjh would enter the circulation and trigger a systemic in ammatory response, mainly affecting in distant organs such as the lung, liver and kidney [24].In our experiment, it was concluded that Ghrelin could reduce oxidative stress after intestinal I/R by promoting mitophagy, thus reducing the release of in ammatory factors and thus avoiding lung injury by the pathological observation of HE staining and the detection of IL-6 and mtDNA levels.…”
Section: Discussionmentioning
confidence: 99%